POLA RELASI PATRON KLIEN DI PESANTREN DARUL FIKRI MALANG - Setiawan, Eko (IAIN Kediri, 2016)
The patron-client relationships were based on unequal exchange, reflecting differences in status. A client (santri), receiving many services from patrons (kiai) so that the client is bound and dependent on patrons. The patron-client relationship is personal. The pattern of the personal reciprocity between kiai and santri create a sense of trust and reliance on the mechanism of the relationship. It can be seen from a culture of respect santri to kiai who tend to be cult. Patron spread thorough, flexible and limitless time frame. The patron-client relationship is put kiai at a high position, influential and authoritative in front of santri. Relation to relation kiai and santri, the santri should be obedient to the kiai.Keywords: Relationships, Patron Klien, Pesantren